Parental control measures to regulate smartphones use by children - Muñoz-Carril, Pablo-César; Souto-Seijo, Alba; Dans-Álvarez-de-Sotomayor, Isabel; Fuentes-Abeledo, Eduardo-José (Psychology, Society & Education, 2023)
The complexity of the current digital ecosystem calls for the development of parental control mechanisms to guide minors in their use of technology. This study aims to identify the type of parental control measures used by parents to monitor the use that school-age children (6 to 12 years old) make of smartphones. An ex post facto design was prepared after conducting a survey in which 885 people (68.7% mothers) took part. The results showed that 93.7% of the parents surveyed used some type of parental control system to regulate the use of the smartphone. The most frequently strategies were limiting the time when the device could be used and restricting access through passwords. The analysis revealed that parents with higher education used a greater number of control mechanisms. Similarly, the length of time the children were connected was related to the level and intensity of the parental control strategies used. Parents applied a greater number of parental control strategies with pre-adolescent children, in the last years of primary education. Finally, the challenges and opportunities that the use of smartphones can bring to children are discussed, and also the active role that the family should play in digital training and education.